Stability Analysis and Design of Support System in Main Adit of Jajarm Bauxite Underground Mines - Sharifzadeh, Mostafa; Shahriar, K.; Ashrafi, E. (n/a, 2008)
Using the bauxite reserves in the district of Jajarm bauxite mines, needs to be excavate by an adit with 800m length. This tunnel is the main haulage means in the first Means of underground mines that passes through limestone rock mass of Mobarak formation, sorkh-shale sedimentary and dolomite rock mass of Elika formation. The rocks consist of highly discontinuous joints, which are considered in stability analysis. In this paper using Rock Mass Classification and Numerical Modeling with UDEC2D4.0, stability of tunnel is analysed and finally suitable supporting system prescribed that consists of steel sets and concrete segments is recommended.